Visitation, communication, and participation: an ethical and respectful strategy for engaging Australian South Sea Islander communities when sharing their lived experiences - Bobongie-Harris, Francis; Youse, Zia; Quakawoot, Gordon (Frontiers in Sociology, 2024)
This study examines the experiences of three Australian South Sea Islanders from the same community who are part of a larger research team scheduled to engage in an archaeological research project in Mackay, Queensland, in 2021. The aim of the project was to highlight Australian South Sea Islander knowledge, voices, and lived experiences. However, owing to COVID-19 and persistent lockdowns in Queensland and New South Wales, the project faced significant delays. The timeline was adjusted, with plans to reintroduce the project to the community after an 18-month hiatus, aiming to rekindle interest and encourage participation. This study focuses on designing a community engagement strategy that builds on established protocols for researchers working with Australian South Sea Islander communities. The strategy includes three key steps: visitation, communication, and participation. By integrating the Tok Stori methodology—an Indigenous research approach from the Solomon Islands and Vanuatu—the strategy supports the decolonisation of the collaborative research process, enabling the sharing of Australian South Sea Islander lived experiences in a culturally safe manner. The authors provide contextualised reflections, offering insights from an Australian South Sea Islander perspective.